Giant pseudopolyps presenting as colocolic intussusception in crohn’s colitis - Atten, Mary Jo; Attar, Bashar M.; Mahkri, Mohammed A.; Del Pino, Alberto; Orsay, Charles P. (The American journal of gastroenterology, 1998)
Bowel obstruction is a well-known complication of Crohn’s disease and is usually a result of stricture formation. Intussusception due to giant pseudopolyps is a rare form of bowel obstruction even in Crohn’s disease. These giant pseudopolyps rarely regress with medical management alone and often require surgical resection.